EFFICIENCY AND EFFECTIVENESS OF ZAKAT PAYROLL SYSTEM AND DIGITAL ZAKAT ON THE ACCEPTANCE OF ZAKAT FUNDS BAZNAS 2016-2017 - DESMADI SAHARUDDIN; RR. TINI ANGGRAINI; SITI JAMILA (Maqdis: Jurnal Kajian Ekonomi Islam, 2019)
This study aims to analyze the level of efficiency and effectiveness of zakat payroll system and digital zakat on the acceptance of zakat funds in BAZNAS2016-2017. This study used the Data Envelopment Analysis (DEA) method with DEA Frontier software, Microsoft Excel 2010 and the Allocation to Collection Ratio (ACR) which compares the distribution ratio with the collection of zakat funds from each program. The results and findings of this study indicate that both the zakat payroll system and digital zakat have a high level of efficiency and effectiveness. This indicates that the community awareness was already high to pay of zakat profession. This research is expected to be a reference for zakat institutions and zakat practitioners in measuring the level of efficiency and effectiveness of a program.